Integration: Achieving Coherence Between Education and Practice in the Professions - Margaret McMillan; Penelope Little (Halla Newcastle Education and Research Center, 2020)
Integrated health services, focused on prevention, anticipate needs and support people to manage conditions, especially in compromised environments. Learning about contemporary, integrated health care is best achieved through integrated approaches to education. Contexts of care are crucial moderators of ways professionals respond to demands. The world of work is complex: In health services measures of safe and therapeutic practice differ across settings; cultures and contexts vary for different client groups; there is a range of capacities and levels of competence within professional and inter-professional groups; and, there are different approaches to managing well in crises. Implicit in successful, rapid responses to crises, are the capable workforces with particular abilities to deal with new situations. The authors suggest that Problem-based Learning (PBL) principles underpinning ideas on integration within and across education and practice, allow for validation of relevant concepts. Goals for Person-Centred Care (PCC) espoused by the World Health Organization apply in a range of situations, including the COVID19 scenario and will be reflected in students' learning outcomes. Given COVID19 challenges, health professions (within healthcare and education systems) recognized the need to adapt and innovate to provide effective patient care and ensure ongoing learning for existing and emerging professionals. Technologies assisted change processes, with limited resources. However, the extent of compromise on levels of integration in practice and education is unknown. Answers to questions posed here will assist with responses to global disruptive phenomena; lessons learned provide direction for management of chronic diseases, healthier living and engagement with the professional education that facilitates rapid responses to novel situations.